CREATION OF SIMULATION MODELS USING THE FLEXSIM SOFTWARE MODULE - Kliment, Marek; Trojan, Jozef; Pekarcíková, Miriam; Kronová, Jana (Advanced Logistic Systems - Theory and Practice, 2022)
All companies and production processes, in the current trend of applying digitization, innovate at all levels of their operation. This trend is an essential factor in maintaining competitiveness in global markets. Companies that have applied digitization and electronic data collection are intensifying these processes and extending them to the next levels of business processes. Those companies that have not used this trend so far are gradually introducing it. Data collection, archiving and transformation is an essential part of accelerating innovative elements in every company. An important factor when working with data is to be able to process it correctly. Elements of digitization are no longer common not only at the level of product modeling, equipment, production lines, but also in the mapping of current older productions, which are still used but are not transformed into a virtual form.